(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
The TNI AD personnel information system (Sisfopers) application is an application that is used to manage personnel data for the TNI AD units. This application is a data processing base for active TNI AD personnel both within the TNI AD structure and outside the TNI AD. The data includes basic data of soldiers from the first appointment to the last position as well as additional data required by the Indonesian Army, both personal and family data. This research was designed to gain an understanding of the implementation of the Indonesian Army Sisfopers, especially at the Military Academy. The purpose of the study was to find out why the implementation of the Indonesian Army Sisfopers at the Military Academy was not optimal and to determine the efforts to improve the Implementation of the Personnel Information System at the Military Academy.This type of research is descriptive qualitative. Data collection techniques used are interviews, observation and literature study. The data analysis method uses data reduction, data display and data verification. The results of the study indicate that the Magelang Military Academy has carried out data updates using the TNI AD Sisfopers application and is in accordance with the standard operating procedures (SOP) contained in the Standard Operating Procedures book regarding the operation of the TNI AD Sisfopers Application and Data Maintenance Activities for Military Academy Personnel in 2020. still not optimal, namely in data update activities there are still delays and at the time of reporting there are still differences in the amount with real conditions. Efforts made by the Akmil are to always coordinate with the staff of the agency personnel department or the administrative staff of unit personnel and carry out synchronization before the report is carried out.